Newcomers, Migrants, Surgeons: Making Career in the Amsterdam Surgeons’ Guild of the Eighteenth Century - Groot, Piet Joannes (TSEG - The Low Countries Journal of Social and Economic History, 2020)
Like many modern organizations, the Amsterdam Surgeons’ Guild recruited its members during the eighteenth century from the ranks of locally born citizens as well as migrants. But how a surgeon’s migration status impacted his chances of being admitted by, and making a career within, the Surgeons’ Guild, remains a mystery. This article analyses enrolment lists of apprentices, journeymen, and master surgeons in order to find out how a surgeon’s birth-place influenced his chances of a career within the Amsterdam Surgeons’ Guild. By looking at the guild’s official stance towards newcomers, and pairing this with the actual career paths of migrants within the Amsterdam Surgeons’ Guild, this article demonstrates that migrants could be retained for the guild if they received their apprenticeship training in Amsterdam. In other words, it was not so much origin, but rather the geography of education and work that shaped careers. These results reveal mechanisms of integration that can be generalised to cases outside the Amsterdam Surgeons’ Guild.